Content of Textbook Entitled â€œPathway To Englishâ€ for the Twelfth Grade of High School - Sianipar, David Ricardo; Ginting, Rahel Lolita; Elisabeth S, Kristina; Saragih, Erikson (JOLLT Journal of Languages and Language Teaching, 2020)
A Textbook has a big role to make the process of learning and teaching running well.Â The good textbook will influence on the studentsâ€™ ability toward the lesson in the classroom. Before getting an explanation from the teachers, the students will learn the material first in their homes. It will let them comprehend the material before being explained by their teachers. It will make the learners easily understanding the lesson which is explained by the teachers in the classroom. By doing so, it will not be complicated for the students in mastering each lesson. The purpose of this research is to know whether the textbook integrates all learning skills and to find out whether the textbook gives assessment or self-reflection to the students about each chapter. In order to do this research, the checklist and documentation method is used to investigate the content of the textbook. The result will be shown by using the table and explained clearly to avoid misunderstanding against the readers. Briefly, a good textbook used by teachers and students in the classroom plays a crucial role in the process of learning and teaching.